DIRECT DAMAGE THAT FOREST FIRES CAUSE TO ROAD INFRASTRUCTURE - Tsekova, Mariana (E-Journal VFU, 2025)
Wildfires are a major and growing threat to road infrastructure, going beyond direct physical damage. This report analyses the damage that wildfires inflict on road infrastructure, encompassing direct damage to materials such as asphalt, concrete and metals. It highlights the complex, reciprocal relationship between roads and wildfires, with roads being both critical access points and significant sources of ignition. The report concludes that integrated and proactive resilience strategies are urgently needed, encompassing prevention, sustainable design, advanced warning systems and equitable recovery strategies.